The dependence of acoustic emission behavior on prior fatigue loading history - Ozevin, Didem; Kessler, Seth (Frontiers in Built Environment, 2022)
Fatigue cracks are a major concern for aging metallic structures, as they can cause unexpected catastrophic failure. They often occur on hidden surfaces, e.g., under paint and rust or on the interface between two structural layers, which makes visual detection difficult. Acoustic Emission (AE) is a passive nondestructive evaluation (NDE) method that measures the initiation and progression of defects when a structure is continuously monitored. While using this method, which has been successfully applied to monolithic and composite structures, the fatigue life is related to the cumulative AE count. However, if the method is applied after the fatigue crack is initiated, the relationship between the fatigue life and the cumulative AE count may not be applicable. In this paper, the dependence of AE behavior on the prior fatigue loading history is studied using modified compact tension specimens. The cumulative AE count, AE correlation plots, and waveform characteristics are shown to be dependent on loading conditions in addition to the coupling state. Relative behaviors between AE sensors and trends in the cumulative AE count are illustrated by two AE characteristics that are shown as being independent of prior loading history and coupling discontinuities.